Technology capability assessment - Methods and applications - Mai, Nguyen Quynh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
This paper is to review and evaluates the technology assessment methods and their expected results and then focus on an approach of technology assessment at national level. The paper ends with the proposal for selecting an appropriate method to meet the objectives of managers and policy makers. Code: 12021801